2013
DOI: 10.5861/ijrsp.2013.450
|View full text |Cite
|
Sign up to set email alerts
|

Affective state, stress, and Type A-personality as a function of gender and affective profiles

Abstract: Three studies were performed to examine positive and negative affect, stress and energy, and Type-A personality as a function of Gender and Affective profiles. In Study I, 304 university students (152 male and 152 female), in Study II, 142 pupils at upper secondary school (95 male and 47 female) and in Study III, 166 pupils at upper secondary school (84 male and 82 female) completed self-report questionnaires pertaining to Positive affect and Negative affect Scales (PANAS), stress and energy (SE), the Type A-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
(57 reference statements)
4
13
0
Order By: Relevance
“…About the relevant differences for sex (but not for classes), results were in line with the previous findings provided by research of De Caroli & Sagone (2016), according to which boys tended to bounce back adversities using humor more than girls; with the findings observed by Schütz et al (2013) and by Schütz, Garcia, & Archer (2014), according to which girls expressed higher levels of negative affect than boys; and, with the evidences of Caprara et al (2006) in the superiority of boys for managing of negative emotions compared to girls in terms of perceived self-efficacy.…”
Section: Discussionsupporting
confidence: 81%
“…About the relevant differences for sex (but not for classes), results were in line with the previous findings provided by research of De Caroli & Sagone (2016), according to which boys tended to bounce back adversities using humor more than girls; with the findings observed by Schütz et al (2013) and by Schütz, Garcia, & Archer (2014), according to which girls expressed higher levels of negative affect than boys; and, with the evidences of Caprara et al (2006) in the superiority of boys for managing of negative emotions compared to girls in terms of perceived self-efficacy.…”
Section: Discussionsupporting
confidence: 81%
“…Across both samples of females, the prevalence of the self-destructive profile was 28%, while among men was 25%. The prevalence of this profile reported here among males and females is the same that was observed among Swedes (Schütz, Garcia & Archer, 2013).…”
Section: Reviewing Manuscriptsupporting
confidence: 87%
“…Finally, since median splits distort the meaning of high and low, it is plausible to criticize the validity of the procedure used here to create the different affective profilesscores just-above and just-below the median become high and low by fiat, not by reality (Schütz, Archer & Garcia, 2013 Reviewing Manuscript affective profile model was replicated using the k-means cluster analysis and the four affective profiles emerged as the combinations of high vs. low affectivity. The procedure used by these researchers is useful for person-oriented analyses (see Bergman, Magnusson et al, 2003), thus, suggesting the original procedure by Archer as valid.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Norlander et al [43] identified four affective profiles: a profile characterized by people who scored high in PA and low in NA (Self-Fulfilling affective profile), a profile with participants who scored low in both dimensions (Low affective profile), other profile characterized by individuals who scored high in PA and NA (High affective profile), and a profile with people who scored low in PA and high in NA (Self-Destructive profile). This typology of affective profiles has been used in subsequent studies, and it has been analyzed in adolescent samples that the Self-Fulfilling profile relates to high scores in life satisfaction or happiness and low scores in depression and stress, whereas the Self-Destructive profile is characterized by the opposite [39,[45][46][47][48][49][50][51]. Consequently, the Self-Fulfilling profile seems to be associated with adaptive dimensions, whereas the Self-Destructive profile associates with maladaptive dimensions.…”
Section: Introductionmentioning
confidence: 99%